Some details of the document advance (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The new medical technology and the recent scientific advances prohang to the extension of the human life, which implies an extension and extension of the life expectancies in the person and the faculty to anticipate and to anticipate the measures and the therapeutic treatments susceptible to be provided arrived the case or,or on the contrary, the reflective refusal or rejection to apply and to make cash medical treatment some when the affected patient is not in the capacity sufficient todecide by itself on the matter. The possible writing arises therefore from a document that can go a head and anticipate such future circumstances.
Keywords: Death; incapacity; forecast; will; dignity.